Features of the Clinical Course of Myocardial Infarction in Type 2 Diabetes - Badritdinova Matluba Nazhmitdinovna; Zhuraeva Khafiza Iskandarovna; Mustafayeva Malika Rustamovna (Genius Journals, 2022)
The features of the clinical course of myocardial infarction in patients with type 2 diabetes mellitus were studied. Among men hospitalized with myocardial infarction, diabetes mellitus was in 56.3%, among women in 72.2%. The mean age of patients with and without DM was 69.9±8.7 and 67.4±7.1, respectively. In patients, painless forms of MI were more common and the anterior and lateral walls of the left ventricle were predominantly affected. In most patients, it was accompanied by severe decompensation of carbohydrate metabolism with high glycemia.
Keywords: myocardial; infarction; glycemia; painless